HUBUNGAN TINGKAT KECUKUPAN ENERGI DAN ZAT GIZI MAKRO DENGAN STATUS GIZI WARGA BINAAN LAPAS ANAK WANITA TANGERANG - Muslimah M, Nur; Angkasa, Dudung; Melani, Vitria (Jurnal Nutrire Diaita (Ilmu Gizi), 2017)
Background: Most women in prison are experiencing inadequate energy and macronutrient intake which may affect their nutritional and health status. Objective: To determine the relationship between the level of energy sufficiency and macro nutrient with nutritional status of women. Method : Cross-sectional data were collected from 100 women prisoner aged 19-45 years old from a major prison in Tangerang City of Indonesia. Weight and height were measured with standard weighing scale and microtoise, respectively and body mass index (BMI) was produced. The prisoner’s intakes were measured by three days 24 hour food recalls. Others observed variables were health seeking behaviour (HSB) and infectious disease history (IDH) which assessed by structured interview questionnaire. Spearman's Rank Test was performed to answer the research questions. Result: There was a positive and weak relationship between energy sufficiency level and nutritional status (p = 0,030), protein adequacy level with nutritional status (p = 0,015), fat sufficiency level with nutritional status (p = 0,034) and carbohydrate sufficiency level with nutritional status p = 0.043). Conclusion: Level of energy and macronutrient intake associate with prison women’s nutritional status.  Keywords: energy sufficiency level and macro nutrient, nutritional status, women